Surigao del Norte [videorecording] a pacific paradise - Medina, Susan Calo.; Philippines. Department of Tourism (Manila Travel Time, 1996)
Describes Surigao del Norte as the paradise in the Pacific, paradise of island and other adventure.
VHS.
Keywords: Surigao del Norte -- Description and travel